Trends in Concurrency, Polygyny, and Multiple Sex Partnerships During a Decade of Declining HIV Prevalence in Eastern Zimbabwe - Eaton, Jeffrey W. (J Infect Dis, 2014)
Background. Observed declines in the prevalence of human immunodeficiency virus (HIV) infection in Zimbabwe have been attributed to population-level reductions in sexual partnership numbers. However, it remains unknown whether certain types of sex partnerships were more important to this decline. Particular debate surrounds the epidemiologic importance of polygyny (the practice of having multiple wives). Methods. We analyze changes in reported multiple partnerships, nonmarital concurrency, and polygyny in eastern Zimbabwe during a period of declining HIV prevalence, from 1998 to 2011. Trends are reported for adult men (age, 17–54 years) and women (age, 15–49 years) from 5 survey rounds of the Manicaland HIV/STD Prevention Project, a general-population open cohort study. Results. At baseline, 34.2% of men reported multiple partnerships, 11.9% reported nonmarital concurrency, and 4.6% reported polygyny. Among women, 4.6% and 1.8% reported multiple partnerships and concurrency, respectively. All 3 partnership indicators declined by similar relative amounts (around 60%–70%) over the period. Polygyny accounted for around 25% of male concurrency. Compared with monogamously married men, polygynous men reported higher levels of subsequent divorce/separation (adjusted relative risk [RR], 2.92; 95% confidence interval [CI], 1.87–4.55) and casual sex partnerships (adjusted RR, 1.63; 95% CI, 1.41–1.88). Conclusions. No indicator clearly dominated declines in partnerships. Polygyny was surprisingly unstable and, in this population, should not be considered a safe form of concurrency.